Einführung der „Qualitätsstandards für die Betriebsverpflegung“ in einem Hamburger Versicherungsunternehmen - Corinna Rohmann (2010)
Ziel dieser Arbeit ist mit Hilfe der Einführung der Qualitätsstandards für die Betriebsverpflegung die aufgezeigten Schwächen zu optimieren. Ebenso soll die Ist- Aufnahme den Wirtschaftsbereich durchleuchten und Optimierungsvorschläge gegeben werden, um die Kundenzufriedenheit für die nächste Befragung zu verbessern. Gleichzeitig werden Anregungen zur Verbesserung des strukturellenund prozessbezogenen Ablaufs gegeben, um den Mitarbeitern ein angenehmes Arbeiten zu ermöglichen.

(untitled)
Purpose The objective of this thesis is to identify potential weaknesses and provide suggestions for optimization in company catering in an insurance company in Hamburg. The analysis is based on the “Quality standards of company catering” developed by the German Association of Nutrition (DGE e.V.). Methods In order to reach the above stated objective, a thorough screening of the food sector in the company was carried out. Within this evaluation the requirements of a healthy nutrition based on the DGE e.V. was inspected. The lunch menus were analysed over four weeks with a computer based program called ‘EBIS pro’. Breakfast, Snacks as well as seminar- and conference catering were analysed based on the three-dimensional Food Guide Pyramid The current state of structural- and process-based areas have been analysed via the discovery and inspection of company internal documentation. Finally the findings have been compared to the guidelines of the quality standards. Results Overall, caterings showed a huge variety of fresh and self-made menus as well as breakfast. Also a daily vegetarian meal and a salad bar. Within the analysis of breakfast and Snacks the content of wholemeal products as well as fruits and vegetables shows a deficit. The lunch showed that too much fat as well as very big portions of meat end up on a consumer’s plate. Vegetable and starch components as well as the iodine feed charge were not able to comply with the recommendations. The hygiene management does not fully meet the legal requirements. Food additives are not declared. Education in nutrition is not given. Conclusion This thesis highlighted the need for sustainable improvements in company catering to give a healthy diet and education in this for working people.